Beware bandwagons! The bandwagon phenomenon in medicine, psychiatry and management. (December 2019) - O'Connor, Nick; Clark, Scott
Objectives: We examined the literature on bandwagons, fashions and fads in the fields of medicine, psychiatry and health management. Conclusions: The bandwagon effect appears to operate across medicine, psychiatry and health management, often to the detriment of patients and health organisations. The authors provide advice on recognising and managing this phenomenon.